Education as important predictor for successful employment in adults with congenital heart disease worldwide. (4th February 2019) - Sluman, Maayke A.; Apers, Silke; Sluiter, Judith K.; Nieuwenhuijsen, Karen; Moons, Philip; Luyckx, Koen; Kovacs, Adrienne H.; Thomet, Corina; Budts, Werner; Enomoto, Junko; Yang, Hsiao‐Ling; Jackson, Jamie L.; et al.
Abstract: Background: Conflicting results have been reported regarding employment status and work ability in adults with congenital heart disease (CHD). Since this is an important determinant for quality of life, we assessed this in a large international adult CHD cohort. Methods: Data from 4028 adults with CHD (53% women) from 15 different countries were collected by a uniform survey in the cross‐sectional APPROACH International Study. Predictors for employment and work limitations were studied using general linear mixed models. Results: Median age was 32 years (IQR 25‐42) and 94% of patients had at least a high school degree. Overall employment rate was 69%, but varied substantially among countries. Higher education (OR 1.99‐3.69) and having a partner (OR 1.72) were associated with more employment; female sex (OR 0.66, worse NYHA functional class (OR 0.67‐0.13), and a history of congestive heart failure (OR 0.74) were associated with less employment. Limitations at work were reported in 34% and were associated with female sex (OR 1.36), increasing age (OR 1.03 per year), more severe CHD (OR 1.31‐2.10), and a history of congestive heart failure (OR 1.57) or mental disorders (OR 2.26). Only a university degree was associated with fewer limitations at work (OR 0.62). Conclusions: There are genuine differences in the impact of CHD on employment status in different countries. Although the majority of adult CHD patients are employed, limitations at work are common. Education appears to be the main predictor for successful employment and should therefore be encouraged in patients with CHD.